A developed failure mode and effect analysis for floating offshore wind turbine support structures - Li, He; Diaz, H.; Guedes Soares, C. (Renewable energy, 2021)
This paper extends the conventional failure mode and effect analysis methodology by introducing weights of its indices that are severity, occurrence, and detection as a basis to analyze the failures of the support structure of a generic floating offshore wind turbine. Critical failure causes, failure modes, as well as systems of the support structure of the floating offshore wind turbine are ascertained. Moreover, based on the analysis, recommendations on corrections and preventive actions are suggested aiming at ensuring the safe and economic operations of the support structure. The validation of the proposed technique is finalized by a comparison study between the results of conventional failure mode and effect analysis methodology and that of the proposed method. The comparison indicates that the proposed technique is more in line with practice and flexible for use and has the merit in removing the limitations of conventional failure mode and effect analysis methodology that different failure causes generate the same risk priority number. •The conventional FMEA is extended to analyze the failures of the support structure of a generic floating wind turbine.•Critical failure causes, failure modes, and systems of the support structure of the floating wind turbine are ascertained.•Recommendations on corrections are suggested aiming at ensuring the safe and economic operation of the support structure.•A comparison is made between the results of conventional FMEA methodology and that of the proposed method.•The proposed technique is more flexible for use and has the merit in partly removing the limitations of conventional FMEA.